Serum Inflammatory Cytokines as Dual Biomarkers in Systemic Lupus Erythematosus and Breast Cancer Progression - Hassan, Abdulrhman M. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Chronic inflammation plays a critical role in both autoimmune diseases and cancer, where cytokines act as key mediators of immune dysregulation. Specific Background: Systemic Lupus Erythematosus (SLE) and breast cancer, despite differing etiologies, share overlapping mechanisms of cytokine imbalance that drive disease progression and immune modulation. Knowledge Gap: However, the potential of inflammatory cytokines as dual biomarkers reflecting both autoimmune and tumor-related processes remains underexplored. Aims: This study aimed to evaluate serum levels of IL-6, TNF-α, IL-1β, IL-8, IL-10, and TGF-β in SLE and breast cancer patients compared to healthy controls, and to analyze their correlation with disease duration. Results: Findings demonstrated significantly elevated pro- and anti-inflammatory cytokine levels in both patient groups (p < 0.001), with strong positive correlations between cytokine concentration and disease duration. Breast cancer patients showed higher IL-6, TNF-α, and TGF-β levels, while SLE patients exhibited pronounced immune activation. Novelty: The study provides the first integrated evaluation of cytokine profiles revealing shared inflammatory signatures in autoimmunity and oncogenesis. Implications: These results highlight cytokines’ potential as diagnostic and prognostic biomarkers, suggesting that cytokine modulation may offer novel therapeutic targets for both SLE and breast cancer.Highlight : Cytokines act as dual biomarkers indicating immune activation in both SLE and breast cancer. Pro- and anti-inflammatory cytokines correlate positively with disease duration and progression. The study highlights cytokines’ potential roles in diagnosis, prognosis, and therapeutic targeting. Keywords : Systemic Lupus Erythematosus, Breast Cancer, Inflammatory Cytokines, IL-6, TNF-α